Maraknya Thrifting dan Transformasi Gaya Hidup Generasi Muda di Kota Makassar - A.Noer Chalifah Ramadhany; Ferdhiyadi Ferdhiyadi; Rusmala Dewi Kabubu (Universitas Negeri Makassar, 2026)
The phenomenon of thrifting or purchasing second-hand clothing has increasingly developed among young people, including in Makassar City. This study aims to analyze the factors driving the rise of thrifting and its relationship with changes in the lifestyle of the younger generation. The research employed a qualitative approach with a descriptive research type. Data collection techniques were conducted through observation, in-depth interviews, and documentation involving thrift business owners and young consumers in Makassar City. The results showed that the growing popularity of thrifting is influenced by economic factors, social media influence, digital fashion trends, and awareness of sustainable fashion. Thrifting is no longer viewed merely as an activity of purchasing second-hand clothing, but has developed into a lifestyle and a symbol of social identity among young people. However, the practice of thrifting still reflects consumerist culture because consumption continues to be influenced by trends and social image. This study concludes that thrifting represents a transformation of urban consumption patterns in the digital era, influenced by the development of social media and modern consumer culture.